Neural Network on Tsunami Waves Prediction Detector Tools Using Tectonic Earthquakes Data - Meta Kallista (Tensor: Pure and Applied Mathematics Journal, 2020)
On 26 December 2004, tsunami waves were generated by undersea megathrust earthquakes particularly hit the Banda Aceh-Indonesia, also Thailand, Sri Lanka, India. The effect of tsunami waves can be very damaging to the coastal areas even more to the land around the coast. It is very interesting to study the relation between the magnitude of the undersea earthquakes and the tsunami. Therefore, we construct an early warning system using Neural Network to predict the tsunami using data from Indonesian Meteorology, Climatology, and Geophysical Agency that integrated with a hardware tool. The hardware tools will show the prediction result and send a short message.